Normal Echocardiographic Parameters of Healthy Adult Individuals working in National Heart Centre - Prajapati, D; Sharma, D; Baidya, SG; Shakya, U; Shrestha, N (Nepalese Heart Journal, 2013)
Background Studies evaluating potential differences in normal cardiac dimensions and body mass indices of various ethnic populations using 2D echocardiography have reported variations based on gender and ethnicity. Currently, accepted echocardiographic reference values are from US studies, and the limited information is available on Nepalese population. The purpose of this study was to derive population-based reference values for two-dimensional (2D) guided M-mode echocardiographic dimensions and left ventricular mass of adult Nepalese that can be applied in epidemiologic studies, clinical trials and clinical practice. Methods 97 individuals were randomly selected, out of 502 staffs working in our hospital, who were over 18 years of age and were free of cardiovascular disease. Subjects underwent M-mode and 2D echocardiogram with color Doppler study. Reference values were derived for end-diastolic and end-systolic left ventricular internal dimensions, left ventricular wall thickness, left atrial dimension, aorta, LV mass. Measurements were described by mean, standard deviation and 95% reference range. Results Echocardiographic measurements were within standard normal limits. The measurements of aorta, left atrium, inter-ventricular septum, left ventricle in systole and diastole, left posterior wall and left ventricular mass, adjusted or not for body surface area, were significantly higher in males. Several echocardiographic measurements, adjusted or not for anthropometric measurements, had different mean and range than the reference limits in US-based studies. Conclusion The means and range for the measurements of left atrium volume, left ventricular diastolic dimension and left ventricular mass found in this survey were lower than those indicated by the international literature and accepted as normal limits. The results of this study strongly indicate the need for a larger scale study to further establish ethnic-specific and gender-specific echocardiographic reference values for the Nepalese population. DOI: http://dx.doi.org/10.3126/njh.v9i1.8339 Nepalese Heart Journal Vol.9(1) 2012 pp.3-6